Configuring a sensor network for fault detection in distributed parameter systems - Patan, Maciej (1975- ); Uciński, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
The problem of fault detection in distributed parameter systems (DPSs) is formulated as that of maximizing the power of a parametric hypothesis test which checks whether or not system parameters have nominal values. A computational scheme is provided for the design of a network of observation locations in a spatial domain that are supposed to be used while detecting changes in the underlying parameters of a distributed parameter system.
Keywords: branch-and-bound; constrained experimental design; distributed parameter systems; fault detection; parameter estimation; sensor location